2021
DOI: 10.1186/s12885-021-08997-w
|View full text |Cite
|
Sign up to set email alerts
|

Immune checkpoint inhibitors plus neoadjuvant chemotherapy in early triple-negative breast cancer: a systematic review and meta-analysis

Abstract: Purpose Some studies have shown that Immune checkpoint inhibitors (ICIs) have a favorable efficacy in advanced triple negative breast cancer (TNBC) patients, but the results are controversial in neoadjuvant chemotherapy (NACT) stage. The purpose of this study is to evaluate the efficacy and safety after NACT plus ICIs in early TNBC patients. Methods After searching PubMed, EMBASE, the Cochrane library and several mainly oncology conferences up to 3… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 52 publications
2
16
0
Order By: Relevance
“…For example, Zhang et al group reported that PD-1/PD-L1 inhibitors in combination with chemotherapy improved pCR (OR 1.59, 95% CI 1.28 to 1.98), event-free survival (HR 0.66, 95% CI 0.48 to 0.91, p = 0.01), and overall survival (HR 0.72, 95% CI 0.52 to 0.99) in TNBC patients compared to chemotherapy alone [ 45 ]. Moreover, Li et al studied the pCR of ICIs in neoadjuvant setting in TNBC and reported that the OR significantly increased in their four included study meta-analysis (OR 2.14, 95% CI 1.37–3.35, P < 0.001) and a better event-free survival (HR 0.66, 95% CI 0.48 to 0.89, P = 0.007) [ 49 ], while similar values for pCR were reported by Rizzo et al (OR 1.95, 95% CI 1.27 to 2.99) and Xin et al (OR 1.91, 95% CI 1.32 to 2.78) [ 46 , 48 ]. Villacampa et al reported that patients with PD-L1-positive tumors had a significantly better PFS with ICIs (HR 0.67, 95% CI 0.58 to 0.79) and a trend towards better OS (HR 0.79, 95% CI 0.60 to 1.03), while no benefit was observed in patients with PD-L1-negative tumors [ 47 ].…”
Section: Discussionmentioning
confidence: 55%
“…For example, Zhang et al group reported that PD-1/PD-L1 inhibitors in combination with chemotherapy improved pCR (OR 1.59, 95% CI 1.28 to 1.98), event-free survival (HR 0.66, 95% CI 0.48 to 0.91, p = 0.01), and overall survival (HR 0.72, 95% CI 0.52 to 0.99) in TNBC patients compared to chemotherapy alone [ 45 ]. Moreover, Li et al studied the pCR of ICIs in neoadjuvant setting in TNBC and reported that the OR significantly increased in their four included study meta-analysis (OR 2.14, 95% CI 1.37–3.35, P < 0.001) and a better event-free survival (HR 0.66, 95% CI 0.48 to 0.89, P = 0.007) [ 49 ], while similar values for pCR were reported by Rizzo et al (OR 1.95, 95% CI 1.27 to 2.99) and Xin et al (OR 1.91, 95% CI 1.32 to 2.78) [ 46 , 48 ]. Villacampa et al reported that patients with PD-L1-positive tumors had a significantly better PFS with ICIs (HR 0.67, 95% CI 0.58 to 0.79) and a trend towards better OS (HR 0.79, 95% CI 0.60 to 1.03), while no benefit was observed in patients with PD-L1-negative tumors [ 47 ].…”
Section: Discussionmentioning
confidence: 55%
“…These observations have been confirmed in two recent systematic reviews and meta-analyses. The first of these, which encompassed six randomized controlled trials focused on early TNBC (n=2142 patients), reported that NAC in combination with PD-1/PD-L1 inhibitors also resulted in improved pCR rates and event-free survival ( 29 ). The second included eight randomized controlled trials, encompassing 4901 patients with both early and metastatic TNBC (four trials in each category) ( 30 ).…”
Section: Discussionmentioning
confidence: 99%
“…Although ICB has made a difference in several cancer indications including melanoma, non-small cell lung cancer, Merkel cell carcinoma, head and neck cancer, and renal cell cancer amongst others, triple negative breast cancer (TNBC) has remained a clinical challenge until the recent FDA approval of pembrolizumab, an anti-PD-1 monoclonal antibody in combination with chemotherapy in early and late stage TNBC (7). Adjuvant chemotherapy, which frequently consists of DNA targeting agents, while necessary, can contribute additional acute toxicity and side effects to the immune-related toxicities inherent in the use of immune checkpoint inhibitors (8)(9)(10)(11)(12)(13)(14). These limitations can negatively impact the quality of life of patients during and after treatment and highlight the need for safer, less toxic anti-cancer agents that can be used in combination with ICB to improve patient outcomes.…”
Section: Introductionmentioning
confidence: 99%